2004
DOI: 10.1007/s00268-004-7507-0
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Duct‐to‐mucosal Pancreaticojejunostomy in pancreaticoduodenectomy

Abstract: This study was conducted to examine the efficacy of duct-to-mucosal pancreaticojejunostomy compared with external stented pancreaticojejunostomy in prevention of several complications, retrospectively. Seventy-six patients with pancreatic head resection (59 male; median age, 60.1 years) underwent pancreaticoduodenectomy at the Second Department of Surgery, Wakayama Medical University, School of Medicine, Wakayama, Japan, between January 1, 1994, and March 31, 2002. In early postoperative status, the incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 26 publications
1
56
0
3
Order By: Relevance
“…Many previous reports have proposed that hard texture of the pancreatic parenchyma and a dilated pancreatic duct have a lower risk of pancreatic fistula formation owing to an ability to prevent pancreatic duct dilatation and shrinkage of the pancreaticojejunostomy after PD [16] . Conversely, in the case of a small pancreatic duct and a soft pancreas, an end-to-end invagination anastomosis or binding pancreaticojejunostomy significantly decreases postoperative complications [20,27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous reports have proposed that hard texture of the pancreatic parenchyma and a dilated pancreatic duct have a lower risk of pancreatic fistula formation owing to an ability to prevent pancreatic duct dilatation and shrinkage of the pancreaticojejunostomy after PD [16] . Conversely, in the case of a small pancreatic duct and a soft pancreas, an end-to-end invagination anastomosis or binding pancreaticojejunostomy significantly decreases postoperative complications [20,27] .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pancreatic fistulas remains a major cause of postoperative complications; it is reported that the incidence of pancreatic fistulas after PD is 6%-25% [4][5][6][7][8][9][10][11][12] . It is known that such pancreatic fistulas induce abscess formation, vascular injuries, rupture of pseudoaneurysms, and postoperative delayed hemorrhage, all resulting from inflammation around leakage sites due to stasis of fluid, including active pancreatic enzymes [13][14][15][16] . The aim of this study was to analyze the independent risk factors for pancreatic fistulas after PD.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a small pancreatic duct size with a soft pancreas creates one of the technical hurdles to the completion of the anastomosis, and is known to be a risk factor for major leakage [3,[8][9][10][11][12][13] . Several methods have been advocated to reduce the occurrence of leakage [5,[14][15][16][17][18][19][20][21] , but the best technique is still a subject of debate [22][23][24][25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…2 The incidence of pancreatic fistula is as high as 24% and it can lead to bleeding, abscess, sepsis and death. [3][4][5][6] Published studies have reported inconsistent outcomes with regards to the effectiveness of internal versus external pancreatic stenting in a patient with pancreaticojejunal anastomosis. There was no substantial variation in morbidity, mortality and hospital stay between the external and the internal pancreatic duct stent groups.…”
Section: Discussionmentioning
confidence: 99%